Globalization and the Industrial Revolution (revised) - Ferreira, Pedro Cavalcanti (2014)
This paper argues that trade specialization played an indispensable role in supporting the Industrial Revolution. We calibrate a two-good and two-sector overlapping generations model to Englandís historical development and investigate how much different Englandís development path would have been if it had not globalized in 1840. The open-economy model is able to closely match the data, but the closed-economy model cannot explain the fall in the value of land relative to wages observed in the 19th century. Without globalization, the transition period in the British economy would be considerably longer than that observed in the data and key variables, such as the share of labor force in agriculture, would have converged to Ögures very distant from the actual ones.